Energy saving in the extractive distillation of isobutyl alcohol–isobutyl acetate with n-butyl propionate - P. S. Klauzner; D. G. Rudakov; E. A. Anokhina; A. V. Timoshenko (Тонкие химические технологии)
Objectives. Determination of the effectiveness of using various types of heat pumps in the extractive distillation of an isobutyl alcohol–isobutyl acetate mixture with n-butyl propionate as the entrainer.Methods. As the main research method, mathematical modeling was performed using the Aspen Plus V. 9 software package. As a model for describing the vapor–liquid equilibrium, the local composition equation-based UNIQUAC model was employed, and the Redlich–Kwong model was adopted to examine the non-ideal vapor phase. When modeling the conventional scheme of extractive distillation, parametric optimization was carried out according to the criterion of total energy costs in the reboilers of the columns. For economical evaluation, Aspen Process Economic Analyzer V10.1 tools were employed. Results. In comparison with the conventional extractive distillation scheme, three variants of schemes with vapor-recompression heat pumps were considered: with a heat pump placed on an extractive distillation column, on an extractive agent regeneration column, and with two heat pumps placed on both columns of the scheme. A scheme with an internal heat pump was also proposed, in which the heat pump compressor is located between sections of extractive columns that operate at different pressures: 506.6 kPa in the top sections and 101.3 in the bottom section. An economic analysis was conducted for all the considered schemes to calculate the total annual costs. It was shown that schemes with vapor-recompression heat pumps can significantly reduce the energy costs of extractive distillation by up to 39.6%; however, a significant reduction in the total annual costs is achieved only with sufficiently long operation periods of the plants. The reduction in the energy costs in the scheme with an internal heat pump was 44%, and the total annual costs were in the range of 20.2–30.1%, depending on the operating time of the plant. Conclusions. It was shown that using heat pumps in the extractive distillation of the mixture of isobutyl alcohol–isobutyl acetate with n-butyl propionate as the entrainer can significantly reduce energy costs. The scheme with an internal heat pump is the most economical of all the considered schemes.